A Comparison of General and Content-Specific Literacy Strategies for Learning Science Content. Issue 2 (3rd April 2017) - Reed, Deborah K.; Whalon, Kelly; Lynn, Devon; Miller, Nicole; Smith, Keely
ABSTRACT: This study employed an adapted alternating treatments single-case design to explore students' learning of biology content when using a general note-taking (GNT) strategy and a content-specific graphic organizer (CGO) to support reading high school biology texts. The 4 focal participants were 15–18-year-olds committed to a moderate risk juvenile justice facility. Lessons were delivered once a week for 7 weeks with CGO delivered first in odd weeks and GNT first in even weeks. When students were unfamiliar with the strategies or experiencing emotional or health problems, their weekly quiz scores tended to be higher on whichever lesson was delivered first. After stabilizing, an average ability reader did better on CGO lessons, and a student with below-average reading ability did better on GNT lessons. CGO took more time to prepare but an average of 11 minutes less than each GNT lesson to implement. CGO also was associated with more student-initiated responses and more self-reported student preferences.